Aboveground woody biomass estimation of green ash trees (Fraxinus pennsylvanica Marsh.) along Colorado's Northern Front Range in response to the invasive emerald ash borer (Agrilus plannipenis Fairmaire) - Truslove, Micaela, author; Mackes, Kurt, advisor; Nagel, Linda, advisor; Davis, Seth, committee member; Paustian, Keith, committee member; Wood, Keith, committee member (Colorado State University. Libraries, 2018)
The invasive emerald ash borer (Agrilus planipennis Fairmaire) has killed hundreds of millions of ash trees (Fraxinus spp.) in forests and urban areas across the United States. Green ash (Fraxinus pennsylvanica Marsh.) is the most widely planted street tree in the greater Denver Metro Area, comprising 15% of the urban tree population on a per-stem basis, and up to 33% of the canopy cover in some cities. EAB is currently established in Boulder, Colorado and as the infestation progresses along the Colorado Northern Front Range, municipalities will need to predict and budget for woody debris disposal from EAB-killed trees. Though existing green ash biomass predictive equations exist, most were developed for areas outside the arid West and generally represent only trees in natural forests, with full, healthy crowns. This study aimed to test whether these equations can accurately predict aboveground woody biomass of green ash trees removed as part of emerald ash borer mitigation efforts in urban areas of Colorado's Northern Front Range. Data from 42 destructively sampled ash trees removed from 11 sites as part of emerald ash borer mitigation efforts were used to evaluate the predictive capability of 12 forest-derived and five urban green ash biomass equations. The published urban equations underpredicted total sampled biomass by as much as 38% and overpredicted by as much as 47%. Forest-derived equations underpredicted by as much as 57% and overpredicted up to 52%. A local, published equation developed in the Northern Front Range overpredicted biomass by 47%. This local urban equation was developed using only open-grown trees with full, healthy crowns while the trees sampled for this study exhibited a broad spectrum of crown conditions, better representing trees that will routinely be removed as part of emerald ash borer management strategies. Sampled trees were also used to develop new local green ash biomass equations, more appropriate for use in emerald ash borer management strategies in Colorado's Northern Front Range cities. In addition, the locally-derived average specific gravity value for green ash wood was 0.57, and the locally-derived average moisture content value was 41%. These are 7.5% higher and 24% lower respectively than widely-used published values. The locally-derived values can be used to further improve the accuracy of urban forest mensuration efforts in Colorado's Northern Front Range.